The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf00053306
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia: intracellular manipulators of mite reproduction

Abstract: Cytoplasmically transmitted Wolbachia (alpha-Proteobacteria) are a group of closely related intracellular microorganisms that alter reproduction in arthropods. They are found in a few isopods and are widespread in insects. Wolbachia are implicated as the cause of parthenogenesis in parasitic wasps, feminization in isopods and reproductive (cytoplasmic) incompatibility in many insects. Here we report on the widespread occurrence of Wolbachia in spider mites and predatory mites based on a PCR assay for a 730 bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
2
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 60 publications
(59 reference statements)
4
131
2
5
Order By: Relevance
“…Spores of the microsporidian pathogen M. phytoseiuli have also never been detected in T. urticae, not even in colonies that were fed to a P. persimilis population that was 100% infected with the microsporidian pathogen. In contrast, Wolbachia may be present in T. urticae as well as in P. persimilis (Breeuwer and Jacobs 1996).…”
Section: Horizontal Transmission Via Residues Of the Mothermentioning
confidence: 92%
See 1 more Smart Citation
“…Spores of the microsporidian pathogen M. phytoseiuli have also never been detected in T. urticae, not even in colonies that were fed to a P. persimilis population that was 100% infected with the microsporidian pathogen. In contrast, Wolbachia may be present in T. urticae as well as in P. persimilis (Breeuwer and Jacobs 1996).…”
Section: Horizontal Transmission Via Residues Of the Mothermentioning
confidence: 92%
“…Until now only five microorganisms detected in P. persimilis have been studied in more detail: the rickettsia Rickettsiella phytoseiuli (Š ut'áková 1991) and Wolbachia sp. (Breeuwer and Jacobs 1996), the microsporidium Microsporidium phytoseiuli (Bjørnson 1998;Bjørnson et al 1996;Bjørnson andKeddie, 1999, 2001) and two non-identified species (Bjørnson and Keddie 2000). Only for M. phytoseiuli clear pathological effects have been reported including negative effects on fecundity, longevity, predation rate and progeny sex ratio (Bjørnson and Keddie, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cultures were maintained, and experiments were performed, in one climate room at 23°C, 60-80% relative humidity, and 16L:8D photoperiod. A polymerase chain reaction (PCR) assay with Wolbachia-specific primers detected that both strains were infected with Wolbachia (Breeuwer and Jacobs 1996). DNA isolation and PCR were as in Breeuwer (1997).…”
Section: Base Populationmentioning
confidence: 99%
“…Tetranychidae Breeuwer and Jacobs (1996) Oligonychus biharensis Tetranychidae Breeuwer and Jacobs (1996) Tetranychus yusti Tetranychidae Breeuwer and Jacobs (1996) Tetranychus kanzawai Tetranychidae Breeuwer and Jacobs (1996) Gomi, Gotoh, and Noda (1997) …”
Section: Eutetranychus Orientalismentioning
confidence: 99%
“…Tetranychidae Breeuwer and Jacobs (1996) Tetranychus turkestani Tetranychidae Breeuwer and Jacobs (1996) Tetranychus quercivorus Tetranychidae Gotoh, Abe, Kurihara, and Suzuki (1995) Tetranychus urticae Tetranychidae Breeuwer andJacobs (1996) Tsagkarakou, Guillemaud, Rousset, andNavajas (1996) Metaseiulus occidentalis Phytoseiidae Johanowicz andHoy (1966) Breeuwer andJacobs (1996) Neoseiulus barkeri Phytoseiidae Breeuwer and Jacobs (1996) Neoseiulus bibens Phytoseiidae Breeuwer and Jacobs (1996) Phytoseiulus persimilis Phytoseiidae Steiner (1993) and Breeuwer and Jacobs (1996) Cardinium sp. …”
Section: Tetranychus Neocaledonicusmentioning
confidence: 99%